Intolerance - Manly, Kate Anna (My University, 1899)
Introduction: Nothing is so dear to the heart of man as a right to his own opinion. Without this, there is no liberty of press, speech or action. Liberty has been the worlds cry for ages. Liberty was the goal for which our forefathers shed their blood; liberty for the down trodden Cubans was the cause for which our brothers, fathers, lovers and husbands only yesterday died. Men rise in the name of justice, and demand liberty; yet few are willing to give it, few are open minded enough to be perfectly tolerant. Intolerance is found in all times, in all classes and on all subjects. Its manifestations differ with the individuals and the times. In ancient days, if a weaker one differed from a stronger in word or deed, he answered for it with his life. Later, he was physically tortured, but his life spared unless the difference was too great. But in the present he is more often ostracized if not nominally, he is practically. It may be from society, church or home from the child who looks with disgust upon the companion that holds there is no Santa, to the gray haired man who spends his latest breath cursing his political rival; from the humble, ignorant cottager who openly asserts that “There aint nobody in the whole community who’s righteous but my Sarah Ann an’ me”.
Citation: Manly, Kate Anna. Intolerance. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Kinds of Intolerance; Race; Social; Political; Religous; Theses; Manuscripts (documents)